Adaption of an ongoing clinical trial to quickly respond to gaps in changing international recommendations: the experience of D2EFT. Issue 1 (19th July 2022) - Papot, Emmanuelle; Jacoby, Simone; Arlinda, Dona; Avihingsanon, Anchalee; Azwa, Iskandar; Borok, Margaret; Brown, Dannae; Cissé, Mohamed; Dao, Sounkalo; Eriobu, Nnakelu; Kaplan, Richard; Karyana, Muhammad; et al.
Abstract: A rapidly changing landscape of antiretrovirals and their procurement at scale has permitted the evaluation of new optimised second-line antiretroviral therapy (ART) in low- and middle-income countries. D 2 EFT is an open-label randomised controlled non-inferiority phase IIIB/IV trial in people living with HIV-1 (PWH) whose first-line non-nucleoside reverse transcriptase inhibitor (NNRTI)-based ART is failing. At inception, it compared a standard of care of boosted darunavir with two nucleos(t)ide reverse transcriptase inhibitors (NRTIs) to the novel NRTI-sparing regimen of boosted darunavir with dolutegravir. Implemented in 2017, participating sites were across Africa, Asia and Latin America. Around the time of implementation, the World Health Organization updated its treatment guidelines and recommended scaling up tenofovir disoproxil fumarate-lamivudine-dolutegravir (TLD). This situation pushed D 2 EFT investigators to consider the impact of the roll-out of TLD on the D 2 EFT research question. The protocol team agreed it was important to study TLD in second-line when an NNRTI regimen was failing, and focused on options to expedite the work by studying the question within the existing trial and network. All key issues (statistical, programmatic and financial) were reviewed to assess the benefits and risks of adding a third arm to the ongoing study, as opposed to developing a new randomised clinical trial with the same control arm and within the same network. The development of a new trial was deemed to be longer than adding a third arm, and to create a challenging situation with two competing clinical trials at the same sites which would slow down recruitment and impair both trials. On the other hand, adding a third arm would be demanding in terms of operationalisation, increased sample size and statistical biases to control. The optimal strategy was deemed to be the addition of a third arm, arriving retrospectively at a simplified multi-arm multi-stage clinical trial design to achieve statistical validity. The D 2 EFT study maintains additional value in a quickly evolving second-line ART strategy allowed by the progress in global access to ART.